Evaluation of Postpartum Pelvic Floor Physical Therapy on Obstetrical Anal Sphincter Injury: A Randomized Controlled Trial. Issue 5 (May 2021) - Von Bargen, Emily; Haviland, Miriam J.; Chang, Olivia H.; McKinney, Jessica; Hacker, Michele R.; Elkadry, Eman
Abstract : Objective: The aim of the study was to evaluate a short course of postpartum pelvic floor physical therapy (PFPT) on symptoms and quality of life after obstetrical anal sphincter injuries (OASIS). Methods: This was a multicenter, randomized controlled trial. Adult women were eligible if they had a vaginal delivery complicated by OASIS and did not have a prior vaginal delivery after 24 weeks' gestation. Participants were randomized to standard care plus PFPT or standard care alone. The primary outcome was change in the Pelvic Floor Distress Inventory (PFDI-20) at 12 weeks postpartum. Secondary outcomes included other validated questionnaires assessing pelvic floor symptoms and bother. Results: We approached 89 eligible women; 50 were enrolled and randomized. We excluded 6 participants in the PFPT group and 1 in the standard care group who withdrew before study initiation or did not provide baseline data at 2 weeks postpartum. Thus, we analyzed 19 in the PFPT group and 24 in the standard care group. The groups were similar with regard to most baseline characteristics. The PFPT group reported significant improvement in pelvic floor symptoms and bother compared with the standard care group, reflected by a decrease of 29.2 (interquartile range = −58.3 to −4.2) compared with 0.0 (interquartile range = −14.6 to 20.8) on the PFDI-20 from 2 to 12 weeks postpartum ( P = 0.002). Significant differences also were observed for all PFDI-20 subscales (all P ⩽ 0.02). Conclusions: At 12 weeks postpartum, the PFPT group reported a significant improvement in pelvic floor symptoms and bother compared with the standard care group.